Holographic ferromagnetic phase transitions with three typical nonlinear electrodynamics in Gauss-Bonnet gravity - Ruo-Tong Wei; Ya-Bo Wu; Te Huang; Jun-Ping Wang; Cheng-Yuan Zhang (Physics Letters B)
At the probe limit, the effects of three typical nonlinear corrections of Born-Infeld electrodynamics (BINE), logarithmic Lagrangian (LNE) and exponential Lagrangian (ENE) on the holographic ferromagnetic model under the four-dimensional Gauss-Bonnet gravity background are studied by numerical calculation. For comparison, the Gauss-Bonnet parameter α is fixed in the article. In the absence of an external magnetic field, three different nonlinear electrodynamic corrections reduce the critical temperature respectively and make the spontaneous magnetic moment more difficult to form. In the case of opening the external magnetic field, the magnetic susceptibility density always satisfies the Curie-Weiss law, and the increase of the nonlinear parameters under the three corrections will prolong the period of the external magnetic field. Comparing the three corrections horizontally, the exponential form of nonlinear electrodynamics correction has a more significant effect on the parameters.